PV generator nominal power estimation using a ground sensor and the PVLIB online irradiance database - Angulo, J.R.; Conde, L.; Muñoz-Cerón, E.; de la Casa, J.; Töfflinger, J.A. (IOP Publishing, 2022)
Abstract The nominal power of a photovoltaic generator is a crucial parameter. For instance, it is a required input parameter for modelling the energy produced by a PV system. Determining the nominal power in-situ requires measuring the irradiance and module temperature. Usually, the irradiance is measured with a sensor placed on the ground and at the plane of the array. The present work first compares the irradiance measurements of a calibrated PV module with the openly available irradiance database PVLIB. Second, it contrasts the daily estimated nominal power values considering both irradiance sources. The results indicate that the irradiance database is suitable to calculate the nominal power.
Keywords: Irradiance; Solar irradiance; Photovoltaic system; Generator (circuit theory); Power (physics); Environmental science; Computer science; Optics; Electrical engineering; Engineering; Physics; Meteorology; https://purl.org/pe-repo/ocde/ford#2.04.00